MEKANISME PENAIKAN VALENSI BAHASA BALI DIALEK NUSA PENIDA (BBDNP) - Suari, A.A. Putu; Artawa, Ketut; Satyawati, made Sri (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 21 (2014): September 2014, 2014)
This article will be concerned with verbal construction in BBDNP. The construction discussed about causatives verb formation. Causativation is related to valency changes of verb. The concept of valence referes to the number of argument that a head may take, in this case the head is the predicate of a clause. Causativation can increase the valence of a verb. Causative processes involve affixes which will be attached on a particular verb. According to this article, affixes of valenecy changes are causative suffix {-ang} and causative suffix {-in}. Both of them mark the BBDNP base, such as a verb, an adjective, a precategorial even state verb. In other side, suffix {-a} can decrease valence of the verb.
Keywords: valence, causative, arguments, affixes